Keseimbangan cinta dan kedamaian dalam pemahaman Tasawuf - Mubarok, Muhammad Fimas Alfin (Maliki Interdisciplinary Journal, 2024)
The values ​​of character education contained in the form of love in the teachings of Sufism are fostering an attitude of harmony in religious, national and state life, sincere in charity, fair in making decisions, responsible, tolerant, democratic, and afraid of hurting fellow human beings because they are seen as a sin. which keeps away from the love of Allah SWT, so as to create peace in society. Love is a fundamental aspect of Sufism, because it is a call to love God wholeheartedly and develop an intimate relationship with Him. However, excessive or unbalanced love can lead to extremism or imbalance in everyday life. Peace is the result of achieving balanced love and includes emotional stability, peace of mind, and harmony in relationships with oneself, others, and the environment. This inner peace allows the individual to face life’s challenges wisely and overcome conflicts in a peaceful way. In this context it can be seen that building a balance between love and peace in the understanding of Sufism is very important. In this modern era full of stress and conflict, this understanding can be a valuable guide for individuals to achieve balance in spiritual life and achieve inner peace.